2005
DOI: 10.1074/jbc.c500193200
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal p73 Isoforms Repress Transcriptional Activity of the Human Telomerase Reverse Transcriptase (hTERT) Promoter

Abstract: Activation of telomerase is linked to tumorigenesis and has been observed in a variety of human tumors. Previous reports demonstrated that p53 represses human telomerase reverse transcriptase (hTERT), a key component for telomerase activity. The p73 protein displays a tumor suppressor activity similar to p53. In the present study, we examined the effect of transactivation competent p73 isoforms on hTERT expression in p53-negative human H1299 cells. Overexpression of C-terminal p73 isoforms (␣, ␤, ␥, ␦) resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 18 publications
(20 reference statements)
1
27
0
2
Order By: Relevance
“…15 However, we did not find any canonical p73/p53 binding site in the minimal p57 promoter. Since it has been previously reported that Sp1 and p53 family members can physically and functionally interact in regulating transcription, [23][24][25] we asked whether p73 could participate in the Sp1-containing complex that binds to p57 promoter. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…15 However, we did not find any canonical p73/p53 binding site in the minimal p57 promoter. Since it has been previously reported that Sp1 and p53 family members can physically and functionally interact in regulating transcription, [23][24][25] we asked whether p73 could participate in the Sp1-containing complex that binds to p57 promoter. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TAp73 is a known transcriptional inducer of ⌬Np73 (Grob et al 2001), but in TAp73-deficient mice a striking increase in ⌬Np73 RNA levels was observed. TAp73 has been reported to repress the expression of several genes by interacting with other transcription factors such as Sp1 in the promoters and regulatory regions of these genes (Salimath et al 2000;Uramoto et al 2004;Innocente and Lee 2005;Racek et al 2005). Many transcriptional repressors have binding sites in the ⌬Np73 promoter, including Sp1 (J. Rosenbluth and J. Pietenpol, unpubl.).…”
Section: Cancer and Infertility: Manifestations Of Genomic Instabilitmentioning
confidence: 99%
“…27 Koutsodontis et al found that the 101 Cterminal amino acids of p53, which include the oligomerization and regulatory domains of the protein, are required for the physical interactions with Sp1. 28 Sp1 has two binding sites in the HBV cp and one in the upstream EII (Fig.…”
Section: Tap73 and δTap73 Directly Interact With Sp1mentioning
confidence: 99%